Evaluation of CEA,CA19-9, and CA242 Tumor Markers in Patients with Colorectal Cancer by ELISA Technique - Ahlam Shakir Hammood AL- Rubaiawi1 Mukhtar Khamis Haba1, Laith Raouf Ahmed AL- Hadad2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Colorectal cancer (CRC) is one of the common malignant tumors of gastrointestinal tract (GIT). A total of 40 patients with CRC were studied preoperatively and postoperatively while only 20 healthy persons were studied. Their ages ranged between 18-78 years.This study was carried out to investigate the possible association of some risk factors with CRC such as (age, gender, smoking, inflammatory bowel disease, and ulcerative colitis). With application of ELISA technique, Serum levels of CEA, CA 19-9, and CA 242 was measured preoperatively and postoperatively. The results showed an increase in preoperative serum level of CEA in CRC patients when compared to both postoperative and control groups, There was a significant increase in the serum level of CEA (10.73 ± 4.01) comparison with the two other groups (postoperative 3.95 ± 1.55) and control (1.91 ± 0.27) at (P<0.05), but no significant differences between the two groups (postoperative and healthy) which have mean (3.95 ± 1.55 and 1.91 ± 0.27) respectively. Also showed a significant increase in serum level of CA19-9 in patients preoperative (23.28 ± 1.86), who were differed significantly from the mean of serum in patients postoperative (18.63 ± 1.40) and control group (19.11 ± 1.46) at (P<0.05), When compared the serum level of CA242 revealed a significant increase in serum level of patients preoperative (19.58 ± 3.46) as compared to postoperative(8.75 ± 1.77) and control group(9.85 ± 2.22) at (P<0.05).